Mental Health Screening: Recognizing and Preventing Mental Health Issues in School-Age Children - Rasmawati, Rasmawati; Muthahharah, Muthahharah; Syisnawati, Syisnawati; Hadrayani, Eka; Amal, Andi Adriana; Rasdiyanah, Rasdiyanah; Nagawati, Nagawati (Journal of Community Engagement in Nursing, 2024)
Mental health issues in children are a significant concern in child development. Mental health problems at this stage are described as serious changes in the way children learn, behave, or handle their emotions, leading to difficulties and challenges in their daily lives. Mental health screening activities are crucial for early identification of children’s mental health issues and providing appropriate interventions. The method employed in this community service activity is screening using the Strengths and Difficulties Questionnaire, followed by providing health education on recognizing and preventing mental health issues in school-age children. Results: screening was conducted on 10 children, revealing mental and emotional condition problems indicated by abnormal scores in total difficulty, emotional problems, conduct problems, and peer problems. There was an increase in students’ knowledge regarding recognizing and preventing mental health issues in children. It is necessary to provide support to students to improve mental health, especially in school-age children.